Research for Global Coordinating Method of Large Equipment Scheduling in Construction Site - Yao Ruojun; Ma Guangwen; Jin Lianghai (Discrete Dynamics in Nature and Society)
Much energy is dissipated when large equipment moves slowly. Generally, equipment scheduling at construction site is supposed to minimize equipment slowdown and deadhead moving. Table methods are always adopted to optimize transfer sequence, but the feasible solution is well disappointing. For the acceptable solution relevant to task points in construction equipment scheduling, transfer table is divided into four regions. After proper augmentation and deflation, the acceptable solution evolves into global coordinating solution of construction scheduling, which contributes to minimizing slowdown and deadhead mileages. This method has been verified in practical engineering and is a significant reference on decision making of construction equipment scheduling.